FAAH rs324420 Polymorphism Is Associated with Performance in Elite Rink-Hockey Players - Silva, Hugo Henrique (2022)
Funding Information: This research was supported by research found ICBAS-PDBiomedical Sciences-200203100 and Portuguese League Against Cancer—Northern Branch (LPCC-NRN).